The blister test : transition from plate to membrane behaviour for an elastic material - Cotterell, Brian (2012)
The crack extension force has been calculated for the blister test when the blister is in transition from plate-like to membrane behaviour. Simple equations are given for the crack extension force that are accurate to better than 1%. The mode-mixity of interfacial fracture in the blister test is discussed and it is shown that the interfacial fracture energy is likely to increase with decrease in thickness of the film. In practical tests, the behaviour of a blister is likely to be nearer to a plate than a membrane.